The Effect of Weight Training on the Kicking Ability of Female Soccer Players in Jember - Fitriani, Siti Dwi; Apriliyanto, Rizki; Hardovi, Bahtiar Hari (Pubmedia Jurnal Pendidikan Olahraga, 2023)
The development of soccer in the world is rapidly advancing, driven by increasingly advanced technology, pushing the world of soccer towards a more modern direction. Soccer has become the most popular sport globally, a sport that can be played by people of all ages and genders. The public's interest in soccer knows no boundaries; anyone can play it. While soccer is predominantly played by men, it is also a sport that can be played by women. Women's soccer in Indonesia is gaining popularity, even though not many women participate in it. Jember Putri is one of the women's soccer clubs in Jember. Improving the athletes' abilities must be carefully considered to enhance the skills and physical endurance of each individual. There are many methods that can be used in athlete development, one of which is weight training.